A consensus protocol for functional connectivity analysis in the rat brain - Grandjean, Joanes; Desrosiers-Gregoire, Gabriel; Anckaerts, Cynthia; Angeles-Valdez, Diego; Ayad, Fadi; Barrière, David A.; Blockx, Ines; Bortel, Aleksandra; Broadwater, Margaret; Cardoso, Beatriz M.; Célestine, Marina; Chavez-Negrete, Jorge E.; et al. (Nature Neuroscience, 2023)
Task-free functional connectivity in animal models provides an experimental framework to examine connectivity phenomena under controlled conditions and allows for comparisons with data modalities collected under invasive or terminal procedures. Currently, animal acquisitions are performed with varying protocols and analyses that hamper result comparison and integration. Here we introduce StandardRat, a consensus rat functional magnetic resonance imaging acquisition protocol tested across 20 centers. To develop this protocol with optimized acquisition and processing parameters, we initially aggregated 65 functional imaging datasets acquired from rats across 46 centers. We developed a reproducible pipeline for analyzing rat data acquired with diverse protocols and determined experimental and processing parameters associated with the robust detection of functional connectivity across centers. We show that the standardized protocol enhances biologically plausible functional connectivity patterns relative to previous acquisitions. The protocol and processing pipeline described here is openly shared with the neuroimaging community to promote interoperability and cooperation toward tackling the most important challenges in neuroscience.
CRIS-Team Scopus Importer:2023-04-07

Brain fMRI Predicts Responses to Certolizumab Pegol in RA. an International, Multi-center, Randomized, Double-blind, Placebocontrolled Trial (PreCePRA) - Rech, Jürgen; Schenker, Hannah; Tascilar, Koray; Hagen, Melanie; Kleyer, Arnd; Simon, David; Mendez, Larissa Valor; Schoenau, Verena; Prade, Jutta; Sergeeva, Marina; Sulvakumar, Mageshvar; Strobelt, Sandra; et al. (ARTHRITIS & RHEUMATOLOGY, 2020)
CRIS-Team WoS Importer:2021-01-15

Central amygdala circuit dynamics underlying the benzodiazepine anxiolytic effect - Griessner, Johannes; Pasieka, Manuel; Böhm, Vincent; Grössl, Florian; Kaczanowska, Joanna; Pliota, Pinelopi; Kargl, Dominic; Werner, Barbara; Kaouane, Nadia; Strobelt, Sandra; Kreitz, Silke; Heß, Andreas; et al. (Molecular Psychiatry, 2021)
Benzodiazepines (BZDs) have been a standard treatment for anxiety disorders for decades, but the neuronal circuit interactions mediating their anxiolytic effect remain largely unknown. Here, we find that systemic BZDs modulate central amygdala (CEA) microcircuit activity to gate amygdala output. Combining connectome data with immediate early gene (IEG) activation maps, we identified the CEA as a primary site for diazepam (DZP) anxiolytic action. Deep brain calcium imaging revealed that brain-wide DZP interactions shifted neuronal activity in CEA microcircuits. Chemogenetic silencing showed that PKCδ+/SST− neurons in the lateral CEA (CEAl) are necessary and sufficient to induce the DZP anxiolytic effect. We propose that BZDs block the relay of aversive signals through the CEA, in part by local binding to CEAl SST+/PKCδ− neurons and reshaping intra-CEA circuit dynamics. This work delineates a strategy to identify biomedically relevant circuit interactions of clinical drugs and highlights the critical role for CEA circuitry in the pathophysiology of anxiety.
CRIS-Team Scopus Importer:2021-02-12

CENTRAL NERVOUS SYSTEM PAIN RESPONSE AND COMPONENTS OF DISEASE ACTIVITY IN RA PATIENTS AFTER TREATMENT WITH CERTOLIZUMAB OR PLACEBO: A POST-HOC ANALYSIS FROM THE PRECEPRA TRIAL - Schenker, Hannah; Rech, Jürgen; Tascilar, K.; Hagen, Melanie; Schoenau, V.; Sergeeva, Marina; Selvakumar, Mageshwar; Konerth, Laura; Prade, Jutta; Strobelt, Sandra; Valor, L.; Hueber, A.; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2020)
CRIS-Team WoS Importer:2020-08-21

Common functional networks in the mouse brain revealed by multi-centre resting-state fMRI analysis - Grandjean, Joanes; Canella, Carola; Anckaerts, Cynthia; Ayrancı, Gülebru; Bougacha, Salma; Bienert, Thomas; Buehlmann, David; Coletta, Ludovico; Gallino, Daniel; Gass, Natalia; Garin, Clément M.; Nadkarni, Nachiket Abhay; et al. (NeuroImage, 2020)
Preclinical applications of resting-state functional magnetic resonance imaging (rsfMRI) offer the possibility to non-invasively probe whole-brain network dynamics and to investigate the determinants of altered network signatures observed in human studies. Mouse rsfMRI has been increasingly adopted by numerous laboratories worldwide. Here we describe a multi-centre comparison of 17 mouse rsfMRI datasets via a common image processing and analysis pipeline. Despite prominent cross-laboratory differences in equipment and imaging procedures, we report the reproducible identification of several large-scale resting-state networks (RSN), including a mouse default-mode network, in the majority of datasets. A combination of factors was associated with enhanced reproducibility in functional connectivity parameter estimation, including animal handling procedures and equipment performance. RSN spatial specificity was enhanced in datasets acquired at higher field strength, with cryoprobes, in ventilated animals, and under medetomidine-isoflurane combination sedation. Our work describes a set of representative RSNs in the mouse brain and highlights key experimental parameters that can critically guide the design and analysis of future rodent rsfMRI investigations.
CRIS-Team Scopus Importer:2019-10-29
Keywords: Connectome; Default-mode network; Functional connectivity; ICA; Seed-based

LONGITUDINAL CHANGE IN THE CENTRAL NERVOUS SYSTEM PAIN RESPONSE AFTER TREATMENT WITH CERTOLIZUMAB OR PLACEBO. A POST-HOC ANALYSIS FROM THE PRECEPRA TRIAL - Rech, Jürgen; Tascilar, K.; Schenker, Hannah; Hagen, Melanie; Sergeeva, Marina; Selvakumar, Mageshwar; Konerth, Laura; Prade, Jutta; Strobelt, Sandra; Schonau, V.; Valor, L.; Hueber, A.; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2020)
CRIS-Team WoS Importer:2020-08-21

Pharmacological and resting state fMRI reveal Osteocalcin’s effects on mouse brain regions with high Gpr37 and Gpr158 expression - Freus, Natalia; Wank, Isabel; Häfele, Maximilian; Kalinichenko, Liubov; Müller, Christian P.; Strobelt, Sandra; Ludwig, Andreas; Heß, Andreas; Kreitz, Silke (Scientific Reports, 2025)
Osteocalcin (OCN) is an endocrine hormone that signals in the periphery, regulating male fertility, energy expenditure and glucose homeostasis. It can also cross the blood-brain-barrier and act on the brain via receptors GPR37 and GPR158. In the brain, OCN influences neurotransmitter synthesis of serotonin, norepinephrine, and dopamine. OCN’s function is related to cognitive and memory performance and lack of OCN is associated with anxiety and depression-like behavior in mice. We used multiparametric magnetic resonance imaging (MRI) including pharmacological MRI and resting state functional MRI, along with gene expression data for Gpr37 and Gpr158 to investigate the physiological effects of intravenously administered OCN on the wild type mouse brain. We found four core brain regions (brainstem, limbic output, association cortex, and basal ganglia) that are highly relevant in all three analytical modalities (i.e. pharmacological, resting state MRI and gene expression) and play therefore a major role in mediating OCN’s effect in the brain. This study provides the first imaging data of the physiological impact of OCN on the mouse brain, suggesting its potential role in modulating brain function and its relevance as a candidate for further investigation in anxiety, depression, and cognitive impairments.
CRIS-Team Scopus Importer:2025-04-01
Keywords: Allen brain atlas; Depression; Functional connectivity; Mouse fMRI; Osteocalcin; rCBV

Prediction of response to Certolizumab-Pegol in rheumatoid arthritis (PreCePRA) by functional MRI of the brain – Study protocol for a randomized double-blind controlled study - Schenker, Hannah; Tascilar, Koray; Konerth, Laura; Sergeeva, Marina; Prade, Jutta; Strobelt, Sandra; Kleyer, Arnd; Simon, David; Mendez, L.; Hagen, Melanie; Schönau, V.; Hueber, A.; et al. (Contemporary Clinical Trials Communications, 2021)
Background: Tumor necrosis factor inhibitors (TNFi) signify a major advance in the treatment of rheumatoid arthritis (RA). However, treatment success initially remains uncertain as approximately half of the patients do not respond adequately to TNFi. Thus, an unmet need exists to better predict therapeutic outcome of biologicals. Objectives: We investigated whether brain activity associated with arthritis measured by functional magnetic resonance imaging (fMRI) of the brain can serve as a predictor of response to TNFi in RA patients. Methods: PreCePRA is a multi-center, randomized, double-blind, placebo-controlled fMRI trial on patients with RA [1] [2]. Active RA patients failing csDMARDs therapy with a DAS28 > 3.2 and at least three tender and/or swollen joints underwent a brain BOLD (blood-oxygen-level dependent) fMRI scan upon joint compression at screening. Patients were then randomized into a 12-week double-blinded treatment phase with 200 mg Certolizumab Pegol (CZP) every two weeks (arm 1: fMRI BOLD signal activated volume > 2000 voxel, i.e. 2 cm3; arm 2: fMRI BOLD signal activated volume <2000 voxel) or placebo (arm 3). DAS28 low disease activity at 12 weeks was assigned as primary endpoint. A 12-week follow-up phase in which patients were switched from the placebo to the treatment arm followed the blinded phase. fMRI was carried out at screening as well as after 12 and 24 weeks of receiving CZP or placebo. Conclusion: We hypothesize that high-level central nervous representation of pain in patients with rheumatoid arthritis predicts response to the TNFi CZP which we further investigate in the PreCePRA trial.
CRIS-Team Scopus Importer:2021-06-04
Keywords: functional MRI; Neuroimaging; Rheumatoid arthritis; TNF inhibition

PREDICTION OF RESPONSE TO CERTOLIZUMAB PEGOL TREATMENT BY FUNCTIONAL MRI OF THE BRAIN: AN INTERNATIONAL, MULTI-CENTER, RANDOMIZED, DOUBLE-BLIND, PLACEBO-CONTROLLED TRIAL (PRECEPRA) - Rech, Jürgen; Tascilar, K.; Schenker, Hannah; Sergeeva, Marina; Selvakumar, Mageshwar; Konerth, Laura; Prade, Jutta; Strobelt, Sandra; Hagen, Melanie; Schonau, V.; Valor, L.; Hueber, A.; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2020)
CRIS-Team WoS Importer:2020-08-21